2010
DOI: 10.1016/j.ejogrb.2009.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of placental abruption: relationship between clinical and histopathological findings

Abstract: Objective We evaluated the extent to which histologic lesions bearing a diagnosis of abruption conform to a diagnosis based on established clinical criteria. We further examined the profile of chronic and acute histologic lesions associated with clinical abruption. Methods Data from the New Jersey-Placental Abruption Study – a multi-center, case-control study – were utilized to compare the clinical and histologic criteria for abruption. The study was based on 162 women with clinically diagnosed abruption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 28 publications
9
58
0
3
Order By: Relevance
“…Other explanations for this difference may be related to different populations and/or different definitions of placental abruption. Furthermore, only about one third of clinically diagnosed abruption cases were confirmed by histopathological examination in this study, similar to an incidence of 30.2% reported by Elsasser et al [11]. Examination of the placenta for conformational purposes has been reported as insensitive, and for that reason a number of reports recommend that the diagnosis of abruption be based on clinical and not histological criteria [10,22].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Other explanations for this difference may be related to different populations and/or different definitions of placental abruption. Furthermore, only about one third of clinically diagnosed abruption cases were confirmed by histopathological examination in this study, similar to an incidence of 30.2% reported by Elsasser et al [11]. Examination of the placenta for conformational purposes has been reported as insensitive, and for that reason a number of reports recommend that the diagnosis of abruption be based on clinical and not histological criteria [10,22].…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have shown a limited correlation between clinical chorioamnionitis and histological chorioamnionitis (HCA) [6,7,8,9]. In the case of placental abruption, several cases have been diagnosed based on histological markers with a clinically unremarkable obstetrical course and outcome and vice versa [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…In 7 patients placental abruption was confirmed by the clinical evidence of adherent blood clots with fibrin deposits after the obstetricians, with more than 15 years of experience in operative obstetrics, performed a careful inspection of the placenta after delivery [18]. 4 abruptions were confirmed microscopically by an experienced (more than 25 years) pathologist, according to recognized criteria of diagnosis [19].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Haste and True Fisp sequences also showed a very good diagnostic efficacy; this was probably due to the coexistence of phases of haemorrhage and ischemia in many cases of bleeding [18].…”
Section: Discussionmentioning
confidence: 96%
“…The criteria for diagnosing a clinical abruption included one or more of the following: painful vaginal bleeding accompanied by nonreassuring fetal status and/or uterine hypertonicity, ultrasonographic visualization of abruption indicating retroplacental anechoicity and/or increased placental thickness (>5 cm), and evidence of retroplacental hemorrhage/clots. 38,39 Nonreassuring fetal status mainly indicated abnormal fetal heart rate patterns, for example, persistent late deceleration, prolonged deceleration, or fetal bradycardia (<110 beats per minute) for 3 minutes or more. Histopathological diagnosis of placental abruption, determined by a pathologist, included retroplacental hematoma and/or villous infarctions associated with decidual destruction.…”
Section: Sample Collectionmentioning
confidence: 99%